THE EFFECTS OF SEASONS ON CHOLESTEROL CONTENT AND FATTY ACID COMPOSITIONS OF MUSCLE OF HELIX ASPERSA LIVING IN KONYA, TURKEY - Citil, Ozcan Baris; Tekeli, Yener; Danahaliloglu, Hatice; Bucak, Serbay (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: The aim of the present study is the determination of the effects of seasonal variations on the proximate analysis, cholesterol content and fatty acid compositions of Helix aspersa. Materials and Methods: Garden snails (Helix aspersa) were picked up by hand from the Central Anatolia Region of Turkey, in autumn (November) and spring (April) in 2011. Fatty acid methyl esters (FAMEs) and cholesterol analysis were analyzed by gas chromatography (GC). The protein contents of snail muscle were determined with Kjeldahl distillation units. Statistical comparisons were made by using SPSS Software (version 16.0).Results: Thirty different fatty acids of different saturation levels were detected. As the predominant fatty acids, stearic acid (C18:0), oleic acid (C18:1ω9), linoleic acid (C18:2ω6), palmitic acid (C16:0), arachidonic acid (C20:4ω6), eicosadienoic acid (C20:2) and linolenic acid (C18:3ω3) were found in Helix aspersa. Palmitic acid (C16:0) was identified as the major SFA in autumn and spring. Linoleic acid (C18:2ω6), eicosadienoic acid (C20:2) and arachidonic acid (C20:4ω6) have the highest levels among the PUFAs. In the present study, ω3 were found 5.48% and 13.94% in autumn and spring, respectively.Conclusion: Linolenic acid and omega-3 fatty acid amounts in the spring increased significantly but cholesterol content was not affected in Helix aspersa both in season.